Stakeholder perceptions in fisheries management - Sectors with benthic impacts. (June 2018) - Soma, K.; Nielsen, J.R.; Papadopoulou, N.; Polet, H.; Zengin, M.; Smith, C.J.; Eigaard, O.R.; Sala, A.; Bonanomi, S.; van den Burg, S.W.K.; Piet, G.J.; Buisman, El; et al.
Abstract: The capture fishing sector causes direct and indirect impacts on benthic habitats and associated fauna and flora. Effectiveness of new mitigation measures depends on fishermen's perceptions; their acceptance of, and compliance to, those measures. Accordingly, by means of Advisory Councils (ACs), fisheries stakeholders are encouraged by the Common Fisheries Policy (CFP) reform to contribute to policy formulations. Still, the CFP reform remains unclear about how to possibly incorporate perceptions of specific conservation measures and objectives in practice. Against this background, this article aims at exploring a systematic multi-criteria approach that provides information about stakeholder preferences for objectives reflecting on what is more important to aim for ('what'), mitigation measures as strategies for reaching their objectives ('how'), and accountability options that can enhance trust in the people who carry out management ('who'). The approach applies a pairwise comparison approach to elucidate the stakeholder preferences, and to estimate the relative importance of the different options. It is conducted in the Black Sea, the Mediterranean Sea, the Baltic Sea, and the North Sea. The outcomes of the questionnaire survey succeed in transparently reflecting a diversity of preferences. It is advised that in order to inform the CFP, the ACs develop a user-friendly attractive online version of this approach that can reach multiple stakeholders across Europe and facilitate updates on a continuous basis. In this way the ACs could better facilitate bottom-up participation in fisheries management by representing a wide range of stakeholder perceptions. Highlights: CFP encourages stakeholder perceptions in fisheries management. Actual implementation of benthic mitigation measures depends on stakeholder perceptions. Stakeholder preferences vary across European regions and stakeholders. Ensuring trust among different stakeholder groups is important through policy making. A digitized tool could enhance future stakeholder engagement in fisheries management.